Undernutrition among rural school-age children: a major public health challenge for an aspirational district in Karnataka, India - Vastrad, Phaniraj; Neelopant, Sushrit; Prasad, U. Venkateswara; Kirte, Rahul; Chandan, N.; Barvaliya, Manish J.; Hatnoor, Shivappa; Shashidhar, S. B.; Roy, Subarna (Frontiers in Nutrition, 2023)
For school-age children, a healthy transition from childhood to adolescence and adulthood depends on proper nutrition. Globally, most nutritional surveys focus on preschool and adolescents, neglecting school-age children. Recent studies have shown the prevalence of thinness among adolescents to be 26.5% in Karnataka. Similarly, among children aged < 5 years in the Raichur district, the prevalence of stunting, wasting, and being underweight was 39.8%, 23.2%, and 40.7%, respectively. The present study aimed to bridge the data gap between < 5 years of children and adolescents through a nutritional survey of school-going children in Raichur, one of the aspirational districts of India.A cross-sectional survey was conducted from January to March 2020 among rural school-age children (n=2700) in thirty villages of the Raichur district of Karnataka, India. The school children were selected through a multi-stage cluster sampling technique. The WHO Anthroplus software was used for calculating the age and sex-specific Z-scores for Weight for Age (WAZ), Height for Age (HAZ), and BMI for Age (BAZ).Results: Of the 2700 school-age children surveyed, the mean weight and height were 22.2 kg (+5.8) and 124.9 cm (+11.6), respectively. The prevalence of children having weight for age Z scores < -2 SD (Underweight) was 45.3% (95% CI: 42.7%-47.8%). The magnitude of stunting and severe stunting was 19.5% (95% CI: 18.0% -21.0%) and 7.6% (95% CI: 6.6%-8.6%), respectively. The proportion of children with BMI for age Z scores < -2SD (thinness) was 43% (95% CI: 41.1%-44.9%), with sub-district Sindhanur having a dual burden of malnutrition.: Despite many flagship programs, the prevalence of undernutrition in school-age children remains a considerable public health problem in the aspirational district of Raichur, India. Further, exploratory studies are recommended to identify the factors associated with undernutrition among school-age children and to strategise evidence-based intervention.